2020
DOI: 10.1128/jvi.01997-19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mollivirus kamchatka , the First Modern Representative of the Proposed Molliviridae Family of Giant Viruses

Abstract: Microbes trapped in permanently frozen paleosoils (permafrost) are the focus of increasing research in the context of global warming. Our previous investigations led to the discovery and reactivation of two Acanthamoeba-infecting giant viruses, Mollivirus sibericum and Pithovirus sibericum, from a 30,000-year old permafrost layer. While several modern pithovirus strains have since been isolated, no contemporary mollivirus relative was found. We now describe Mollivirus kamchatka, a close relative to M. sibericu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
(44 reference statements)
0
36
0
Order By: Relevance
“…For instance, the viruses with the largest known genomes so far, the pandoraviruses, exhibit a regionalized enrichment of core genes in the first half of their genomes [51]. A similar dichotomous distribution was revealed in the distantly related molliviruses, where genes shared between molliviruses and pandoraviruses are also co-localized in half of their genomes [52]. Likewise, in faustoviruses, sequence conservation is not uniformly distributed, although it displays a different pattern with greater sequence divergence in the middle of the genome and at the extremities [39].…”
Section: Discussionmentioning
confidence: 76%
“…For instance, the viruses with the largest known genomes so far, the pandoraviruses, exhibit a regionalized enrichment of core genes in the first half of their genomes [51]. A similar dichotomous distribution was revealed in the distantly related molliviruses, where genes shared between molliviruses and pandoraviruses are also co-localized in half of their genomes [52]. Likewise, in faustoviruses, sequence conservation is not uniformly distributed, although it displays a different pattern with greater sequence divergence in the middle of the genome and at the extremities [39].…”
Section: Discussionmentioning
confidence: 76%
“…In prokaryotes, the analysis of the co-occurrence of R-M systems and genetic fluxes between bacteria revealed that genetic exchanges are favored between genomes that share the same R-M systems, regardless of their evolutionary distance 53 . A similar phenomenon might be at play between molliviruses and pandoraviruses, and partially explains their shared gene content 52 . Previous analyses have also suggested that amoeba act as a genetic melting pot between intracellular bacteria 54 , a concept that should now be extended to include amoeba-infecting viruses.…”
Section: Discussionmentioning
confidence: 77%
“…If we previously noticed that some genes might be swapped between strains of pandoraviruses 38 , the present case involves an exchange between viruses from totally different families only sharing the Acanthamoeba host. In the recently discovered mollivirus kamchatka 52 , a MTase without ortholog in Mollivirus sibericum was probably acquired from a pandoravirus. In prokaryotes, the analysis of the co-occurrence of R-M systems and genetic fluxes between bacteria revealed that genetic exchanges are favored between genomes that share the same R-M systems, regardless of their evolutionary distance 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to cellular genomes, giant virus genomes undergo both expansive and reductive genome evolution. The increased genome size in giant viruses can be attributed to gene duplications, de novo gene origination, and lateral gene transfers (LGTs, or horizontal gene transfers [HGTs]) from cellular organisms or other viruses [ 13 , 55 , 56 , 135 , 136 , 137 ]. Among these sources, LGTs generally bring in more innovative functions to viral genomes.…”
Section: Evolution Of Genome Contentmentioning
confidence: 99%